The Influence of Price, Electronic Word of Mouth (EWOM), E-Service Quality on Customer Loyalty Using Maxim Online Transportation in Jakarta - Silla Macripah; Idha Nurmaulidya; Yana Tatiana; Nunuh Nunuh (Jurnal Ilmu Multidisiplin, 2025)
This study aims to analyze and prove the influence of Price, Electronic Word of Mouth, and E-service Quality and their impact on customer loyalty in Maxim online transportation services. Utilizing a quantitative research methodology, data was collected through surveys of Maxim’s users. The research population in this study are customers of Maxim's online transportation services in Jakarta. The sampling technique uses purposive sampling with a total sample of 100 respondents. The data analysis method used SPSS 29. The study results show that Price and Electronic Word of Mouth (eWOM) do not influence customer loyalty. Meanwhile, E-Service Quality has a positive and significant influence on Maxim customer loyalty in Jakarta. Simultaneously, the variables Price, Electronic Word of Mouth (eWOM), and E-Service Quality have a positive and significant influence on Maxim customer loyalty in Jakarta.